Christianity and radical democracy in the Philippines building a church of the poor - Moxham, Christopher (Routledge studies in Asian religion and philosophy, 2023)
"This book analyses faith-based development action in the Philippines by studying Catholic social movements and development studies in Southeast Asia. By drawing upon primary, qualitative data, this book examines cultural production and community resilience amid poverty and structural restraints. It also interrogates the discourse of Basic Ecclesial Communities, the smallest organisational unit of the Philippine Catholic Church, to better understand the strengths and weaknesses of the social movement. The author shows that the dream of local economic development and empowerment requires help from the Catholic hierarchy, particularly the organizational and leadership resources at the diocese level. This book is a unique contribution in opening up interdisciplinary approaches to religion, faith and social development. It will be of interest to researchers on Asian Studies, especially Southeast Asian Studies, Development Studies, the Anthropology of Development, Social Movements, and the Anthropology of Christianity, Missiology and Religious Studies"--